High Dose Lopinavir/Ritonavir Does Not Lead to Sufficient Plasma Levels to Inhibit SARS-CoV-2 in Hospitalized Patients With COVID-19 - Karolyi, Mario; Omid, Sara; Pawelka, Erich; Jilma, Bernd; Stimpfl, Thomas; Schoergenhofer, Christian; Laferl, Hermann; Seitz, Tamara; Traugott, Marianna; Wenisch, Christoph; Zoufaly, Alexander (Frontiers in Pharmacology, 2021)
Background: Despite lopinavir/ritonavir (LPV/RTV) demonstrating in-vitro activity against SARS-CoV-2, large trials failed to show any net clinical benefit. Since SARS-CoV-2 has an EC50 of 16.4 μg/ml for LPV this could be due to inadequate dosing. Methods: COVID-19 positive patients admitted to the hospital who received high dose LPV/RTV were included. High dose (HD) LPV/RTV 200/50 mg was defined as four tablets bid as loading dose, then three tablets bid for up to 10 days. Trough plasma concentrations were measured after the loading dose and on day 5–7 in steady state (SS). Post loading dose (PLD) and SS plasma trough levels were compared with SS trough levels from COVID-19 patients who received normal dose (ND) LPV/RTV (2 tablets bid) at the beginning of the pandemic. Results: Fifty patients (30% female) with a median age of 59 years (interquartile range 49–70.25) received HD LPV/RTV. Median HD-PLD concentration was 24.9 μg/ml (IQR 15.8–30.3) and significantly higher than HD-SS (12.9 μg/ml, IQR 7.2–19.5, p < 0.001) and ND-SS (13.6 μg/ml, IQR 10.1–22.2, p = 0.013). HD-SS and ND-SS plasma levels did not differ significantly (p = 0.507). C-reactive-protein showed a positive correlation with HD-SS (Spearman correlation-coefficient rS = 0.42, p = 0.014) and ND-SS (rS = 0.81, p = 0.015) but not with HD-PLD (rS = 0.123, p = 0.43). Conclusion: HD-PLD plasma trough concentration was significantly higher than HD-SS and ND-SS concentration, but no difference was detected between HD-SS and ND-SS trough levels. Due to the high EC50 of SARS-CoV-2 and the fact that LPV/RTV is highly protein bound, it seems unlikely that LPV/RTV exhibits a relevant antiviral effect against SARS-CoV-2 in vivo.